2018
DOI: 10.3892/or.2018.6930
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑486‑5p functions as a tumor suppressor of proliferation and cancer stem‑like cell properties by targeting Sirt1 in liver cancer

Abstract: Cancer stem-like cells (CSCs) are critical for the initiation, progression, chemoresistance and postsurgical recurrence of liver cancer. They are thought to be novel targets for the treatment of liver cancer, however, efficient agents that target liver cancer stem cells (CSCs) have not been identified. MicroRNAs (miRNAs) are small non-coding RNAs that target the 3'untranslated region (3'UTR) of mRNAs. Their dysregulation has been implicated in several types of cancer including liver cancer, but it still remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 35 publications
4
20
0
Order By: Relevance
“…Moreover, we demonstrated that the anti-miR-486-mediated anti-inammatory response in LPSstimulated macrophages was antagonized by SIRT1 inhibition. Similar to our work, SIRT1 was earlier demonstrated to be a direct functional target of miR-486 in erythroleukemia cells, 14 liver cancer stem-like cells 15 and human adipose tissue-derived mesenchymal stem cells. 16 Additionally, recent studies elucidated that several other miRNAs regulated the inammatory responses of macrophages through targeting SIRT1, such as miR-138 and miR-199a.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, we demonstrated that the anti-miR-486-mediated anti-inammatory response in LPSstimulated macrophages was antagonized by SIRT1 inhibition. Similar to our work, SIRT1 was earlier demonstrated to be a direct functional target of miR-486 in erythroleukemia cells, 14 liver cancer stem-like cells 15 and human adipose tissue-derived mesenchymal stem cells. 16 Additionally, recent studies elucidated that several other miRNAs regulated the inammatory responses of macrophages through targeting SIRT1, such as miR-138 and miR-199a.…”
Section: Discussionsupporting
confidence: 89%
“…12,13 Moreover, SIRT1 was demonstrated to act as a functional target of miR-486 in several other diseases. [14][15][16] However, the effect of interplay between miR-486 and SIRT1 in sepsis remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…miR-365 directly regulated Ras-related C3 botulinum toxin substrate 1 (RAC1) by binding with the mRNA 3 UTR and affected HCC drug resistance (Jiang et al, 2019). In addition, miR-486 directly targeted sirtuin1, which exhibits high expression in self-renewing and tumorigenic LCSCs (Yan et al, 2019).…”
Section: Mir-26b-5pmentioning
confidence: 99%
“…Many studies have reported the abnormal expression and biological function of miRNAs in liver cancer. For example, miR-486 is obviously down-regulated in liver cancer, and its ectopic expression can hinder the occurrence of tumor [10]. MiR-498 inhibits growth and metastasis of liver cancer by targeting and down-regulating the expression of ZEB2 [11].…”
Section: Introductionmentioning
confidence: 99%